The effect of surgical cure of primary hyperparathyroidism on cardiac electrical activity: a cross−sectional study - Kmieć, Piotr; Karwacka-Bujak, Izabela; Bohdan, Michał; Świątkowska-Stodulska, Renata; Sworczak, Krzysztof (Frontiers in Endocrinology, 2025)
Cardiovascular complications are not assessed routinely in the management of primary hyperparathyroidism (pHPT), nor do they constitute indications for surgical treatment of this disorder. Research concerning the effects on cardiac electrical activity in PHPT is scarce. In the current study, 45 consecutive pHPT patients with hypercalcemia and elevated parathyroid hormone levels were assessed clinically, biochemically and by 24-h ECG monitoring before, one and six months after curative parathyroidectomy (PTX). There were 41 female and four male subjects, their mean age was 54.6 ± 14.6 years. 20 patients were normotensive and 25 had previously or newly diagnosed hypertension. Patients without hypertension compared to the hypertensive ones had lower BMI: 23.2 (20.3-25.4) versus 26.7 (24.8-28.4), higher total calcium: 11.9 ± 0.8 versus 11.3 ± 0.9 mg/dL, and shorter QTc: 418 ± 17 versus 436 ± 17 ms, p<0.001. Before surgery, Ca and PTH correlated negatively with QTc. Upon curative PTX, the median number of supraventricular premature beats (SVPBs) and ventricular premature beats (VPBs) decreased significantly, which was paralleled by a 37% decrease in the prevalence of clinically significant SVPBs (>76 per 24h), and a 29% decrease in the number of patients with more than 3 VPBs/24h six months after surgery. QTc increased from 428 ± 19 before to 441 ± 17 ms after PTX. The change in the median number of SVPBs and VPBs was comparable between patients with versus without HT. Curative PTX normalizes QTc, reduces supraventricular and ventricular extrasystoles in patients with hypercalcemic pHPT.